2004
DOI: 10.1080/14786430410001678136
|View full text |Cite
|
Sign up to set email alerts
|

Bosonic mode interpretation of novel scanning tunnelling microscopy and related experimental results, within boson–fermion modelling of cuprate high-temperature superconductivity

Abstract: This paper seeks to synthesize much recent work on the HTSC materials around the latest energy resolved scanning tunnelling microscopy (STM) results from Davis and coworkers.The STM conductance diffuse scattering results in particular are employed as point of entry to discuss bosonic modes, both of condensed and uncondensed form. The bosonic mode picture is essential to understanding an ever growing range of observations within the HTSC field. The work is expounded within the context of the site-inhomogeneous … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 145 publications
0
12
0
Order By: Relevance
“…As one moves into the OD region, Im along (π, π) becomes purely quadratic (at least up to 100 meV) [105]. Away from the nodes, it has proved difficult to determine the precise form of Im (ω) since the lineshapes are invariably broad and the qp states incoherent, due presumably to a strong dressing or scattering of the charge carriers in this region in k-space [107][108][109]. Kaminski et al showed in fact that the qp states near (π , 0) become incoherent above a certain dopingdependent temperature which coincides with the onset of Tlinear resistivity and is labelled T coh in figure 2 [51].…”
Section: Anisotropic Quasiparticle Scatteringmentioning
confidence: 99%
“…As one moves into the OD region, Im along (π, π) becomes purely quadratic (at least up to 100 meV) [105]. Away from the nodes, it has proved difficult to determine the precise form of Im (ω) since the lineshapes are invariably broad and the qp states incoherent, due presumably to a strong dressing or scattering of the charge carriers in this region in k-space [107][108][109]. Kaminski et al showed in fact that the qp states near (π , 0) become incoherent above a certain dopingdependent temperature which coincides with the onset of Tlinear resistivity and is labelled T coh in figure 2 [51].…”
Section: Anisotropic Quasiparticle Scatteringmentioning
confidence: 99%
“…The second term (seen by ARPES) has been attributed to scattering off a bosonic mode, though its origin and its relevance to high-T c superconductivity remain subjects of intense debate. 26 Possible candidates include phonons, d-wave pairing fluctuations, spin (large-q) fluctuations and charge (small-q) fluctuations but since all, bar phonons, appear to vanish in heavily overdoped non-superconducting cuprates, 11,27,28 it is difficult to single one out at this stage. Nevertheless, if this bosonic mode is the source of the anisotropic scattering revealed by AMRO, the continuation of its linear T-dependence to very low temperatures implies the presence of a surprisingly low energy scale.…”
mentioning
confidence: 99%
“…The second term (seen by ARPES) has been attributed to scattering off a bosonic mode, though its origin and its relevance to high-T c superconductivity remain subjects of intense debate 26 . Possible candidates include phonons, d-wave pairing fluctuations, spin and charge fluctuations but as all, bar phonons, seem to vanish in heavily overdoped non-superconducting cuprates 11,27,28 , it is difficult to single one out at this stage.…”
mentioning
confidence: 99%
“…Whilst there is a growing body of evidence for saturation and a quadratic frequency dependence in cuprates, particularly along the nodal direction, there is mounting evidence too for some form of strong bosonic feature in the anti-nodal regions near the Brillouin zone boundaries, 49,50,51 the origin of which remains controversial. 52,53,54 This contribution to Γ(φ,T ,ω) should also be explored within the present phenomenology for completeness. What we would argue however is that since scattering is already so intense at (π, 0), the true, 'ideal' form of Γ(ω) (and ImΣ(ω)) in this region of the Brillouin zone inevitably will be significantly renormalized due to the overarching presence of Γ MIR , masking the inherent nature of Γ(ω) in many of the physical properties that are measured.…”
Section: Discussionmentioning
confidence: 98%